Design and simulation of half-bridge power supply - 239784 Goey, Hee Tat (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2006